Genetic variability of five ADRB2 polymorphisms among Mexican Amerindian ethnicities and the Mestizo population - Salas-Martínez, María Guadalupe (PLoS One, 2019)
The Mexican population is characterized by high and particular admixture, and the picture of variants associated with disease remains unclear. Here we investigated the distribution of single nucleotide polymorphisms (SNPs) in the Mexican population. We focused on two non-synonymous and three synonymous SNPs in the beta-2 adrenergic receptor gene (ADRB2), which plays key roles in energy balance regulation. These SNPs were genotyped in 2,011 Mexican Amerindians (MAs) belonging to 62 ethnic groups and in 1,980 geographically matched Mexican Mestizos (MEZs). The frequency distribution of all five ADRB2 variants significantly differed between MAs, MEZs, and other continental populations (CPs) from the 1000 Genomes database. Allele frequencies of the three synonymous SNPs rs1042717A, rs1042718A, and rs1042719C were significantly higher in Mexican individuals, particularly among MAs, compared to in the other analyzed populations (P<0.05). The non-synonymous ADRB2 Glu27 allele (rs1042714G), which is associated with several common conditions, showed the lowest frequency in MAs (0.03) compared to other populations worldwide. Among MEZs, this allele showed a frequency of 0.15, intermediate between that in MAs and in Iberians (0.43). Moreover, Glu27 was the only SNP exhibiting a geographic gradient within the MEZ population (from 0.22 to 0.11), reflecting admixed mestizo ancestry across the country. Population differentiation analysis demonstrated that Glu27 had the highest F(ST) value in MAs compared with Europeans (CEU) (0.71), and the lowest between MAs and Japanese (JPT) (0.01), even lower than that observed between MAs and MEZs (0.08). This analysis demonstrated the genetic diversity among Amerindian ethnicities, with the most extreme F(ST) value (0.34) found between the Nahuatls from Morelos and the Seris. This is the first study of ADRB2 genetic variants among MA ethnicities. Our findings add to our understanding of the genetic contribution to variability in disease susceptibility in admixed populations.